Buyer Quality and Procurement Outcomes: Explorative Evidence From the US - Giancarlo Spagnolo; Francesco Decarolis; Elisabetta Iossa; Vincenzo Mollisi; Leonardo Giuffrida (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2016)
We explore empirically the impact of buyer quality on public procurement outcomes. Using purchases data (Federal Procurement Data System) and survey data (Federal Employee Viewpoint Survey) from US federal agencies, we find that procurement quality is highly heterogeneous across different agencies and persistent over time. The qualitative aspect that better predicts procurement performance is the perceived degree of cooperation within the unit, followed by the presence of appropriate incentives. We then assess the main channels through which public procurer quality affects outcomes. We find that buyer quality improves the selection of suppliers and strengthens the association between the use of cost plus contracts and the negotiation procedure.
Keywords: D44; H11; H57; 330; Buyer Quality; Competence; Management practices; Procurement